Procedures for Using Rental Shop Houses (Ruko) and Legal Responsibilities on PT. Kereta Api Indonesia Land - Subagjo, Ichwal; Wibowo, Teguh; Wijaya Damayanti, Aurelia Wahda (LEGAL BRIEF, 2024)
Currently, there is a lot of use of land assets of PT. KAI which is used for activities outside the railway. In order to achieve land use in accordance with applicable land law, appropriate and ideal policies are needed. In this research, the problems are divided into the procedures for renting shop houses (Ruko) on the land of the Indonesian Railways Limited Company (PT. KAI) and relating to legal responsibility if one of the parties violates the agreement or regulations that apply to the process of implementing a rental agreement for a Shop House (Ruko). This research is legal research with normative research methods. The results of this research show that in the shophouse rental process there are several stages that must be carried out, namely: property announcement, application submission by prospective tenants, document verification, location survey, offer and negotiation, to contract signing and initial payment. In connection with applicable legal responsibilities in accordance with the provisions of the contract and applicable law. Parties who violate may be subject to various sanctions, including fines, termination of the contract, or the obligation to compensate for losses arising from the violation. Tenants who fail to fulfill their obligations in payment, maintenance or use of the property according to the agreement can be evicted and asked to pay compensation. On the other hand, if PT KAI as the lessor fails to fulfill its obligations, such as delivering the property in proper condition or carrying out necessary maintenance, they may have to provide compensation or face legal action from the lessee